Pengaruh Kualitas Pelayanan, Kualitas Produk, dan Persepsi Harga terhadap Kepuasan Konsumen KFC Cikini, Jakarta Pusat - Noviherni; Elon Manurung; Anisa Mulia Rachman S (JOURNAL INTELEKTUAL, 2024)
Introduction/Main Objectives: To empirically test whether service quality, product quality, and price perception have an effect on consumer satisfaction at KFC Cikini, Central Jakarta. Background Problems: The large number of fast food restaurants has created special competition between fast food restaurants so that various methods are used by each fast food restaurant to win the competition. Novelty: Retesting the same variables by previous researchers, by analyzing different objects and subjects and different analysis tools. Research Methods: This study uses primary data, the sample in the study was 100 KFC Cikini consumer respondents, the data collection technique used a questionnaire via Google form and used descriptive analysis and Structural Equation Model (SEM-PLS) 3.2.8. Finding/Results: That service quality, product quality and price perception have a significant effect on consumer satisfaction at KFC Cikini, Central Jakarta. Conclusion: Product quality has the most dominant influence on consumer satisfaction because KFC has quality products, so that KFC should focus on the quality of service and the pricing strategy provided to make consumers feel satisfied and happy to increase the target market.